Mapping Green Tax Research Trends: A Bibliometric Analysis Study - Bima, Muhammad; Alim, Mohammad Nizarul (Ilomata International Journal of Tax and Accounting, 2024)
A green tax is a type of tax that is applied to reduce the amount of pollution and preserve the green environment. This research focuses on the results of mapping research articles on the topic of green taxes from Scopus-indexed international journal literature Q1 (quartile 1) to Q4 (quartile 4) for the period 2015-2024. The purpose of this research is to examine more deeply about green tax research with a bibliometric analysis study focusing on the subject areas of environmental science, energy, economics, econometrics and finance, social sciences, engineering, business management and accounting, computer science. This research uses a descriptive quantitative approach with simple statistical analysis on bibliometric analysis. Bibliometric analysis is used to know future research trends on green taxes. This research also includes visualization analysis results from data processing results with Vosviewer. The results of the study have found 182 articles from Scopus-indexed journals Q1 (quartile 1) to Q4 (quartile 4). The contribution of this research is that it can provide future directions in determining innovative green tax design and distribution effect analysis and provide insights that have value for policymakers in sustainable development.